Pelatihan Keterampilan Dasar Kewirausahaan di Pondok Pesantren Baitussholihin - Jemi Cahya Adi Wijaya Adi Wijaya; Putu Ngurah Rusmawan; Rochmad Eko (CV SWA Anugerah, 2023)
The training activities aimed at opening insights and instilling the spirit and confidence of young entrepreneurs to do business through UMKM activities. In addition to insight and enthusiasm, through these training activities also the centers will be given knowledge and some basic skills that a true entrepreneur should possess such as: Spirit entrepreneurial, ways to create Business Opportunities, Business Ethics, Business Plan and Partnership Enterprise, Accounting Small Enterprises, Negotiation and Business Communication, Tips - marketing tips UMKM products, comments and Sharing sessions. Almost the entire Baitussholihin residence has creative ideas for entrepreneurship, so it can be concluded that BaitusSholihin is a community with an upper middle economy. This has the effect that the training of basic entrepreneurial skills that will be carried out will not give difficulties to the manager in terms of the means of motivation.